Research priorities and potential methodologies to inform care in subsequent pregnancies following stillbirth: a web-based survey of healthcare professionals, researchers and advocates - Wojcieszek, Aleena M (BMJ Open, 2019)
OBJECTIVES: To identify research priorities and explore potential methodologies to inform care in subsequent pregnancies following a stillbirth. DESIGN: Web-based survey by invitation. PARTICIPANTS: Multidisciplinary panel of 79 individuals involved in stillbirth research, clinical practice and/or advocacy from the international stillbirth research community (response rate=64%). OUTCOME MEASURES: Importance of 16 candidate research topics and perceived utility and appropriateness of randomised controlled trial (RCT) methodology for the evaluation of four pertinent interventions: (1) medical therapies for placental dysfunction (eg, antiplatelet agents); (2) additional antepartum fetal surveillance (eg, ultrasound scans); (3) early planned birth from 37 weeks’ gestation and (4) different forms of psychosocial support for parents and families. RESULTS: Candidate research topics that were rated as ‘important and urgent’ by the greatest proportion of participants were: medical therapies for placental dysfunction (81%); additional antepartum fetal surveillance (80%); the development of a core outcomes dataset for stillbirth research (79%); targeted antenatal interventions for women who have risk factors (79%) and calculating the risk of recurrent stillbirth according to specific causes of index stillbirth (79%). Whether RCT methodologies were considered appropriate for the four selected interventions varied depending on the criterion being assessed. For example, while 72% of respondents felt that RCTs were ‘the best way’ to evaluate medical therapies for placental dysfunction, fewer respondents (63%) deemed RCTs ethical in this context, and approximately only half (52%) felt that such RCTs were feasible. There was considerably less support for RCT methodology for the evaluation of different forms of psychosocial support, which was reinforced by free-text comments. CONCLUSIONS: Five priority research topics to inform care in pregnancies after stillbirth were identified. There was support for RCTs in this area, but the panel remained divided on the ethics and feasibility of such trials. Engagement with parents and families is a critical next step.